Recent Patents on Nanoporous Filtration Membranes with Complex Pores - Zhang, Yongbin (Recent Patents on Engineering, 2020)
Background: The challenges to nanoporous filtration membranes are small fluxes and low membrane mechanical strengths. Objective: To introduce newly invented nanoporous filtration membranes with complex pores, improved fluxes and mechanical strengths as registered in patents. Methods: The analytical results are presented for the addressed membranes. Results: The geometrical parameter values of the addressed membranes can be optimized for the highest fluxes. Conclusion: The overall performances of nanoporous filtration membranes with complex cylindrical or/and conical pores can be significantly better than that of the conventional nanoporous filtration membranes with single cylindrical or conical pores.
Keywords: Conical pore